Correlation of clinical features, thyroid status and endometrial histopathology in abnormal uterine bleeding - Deshmukh, Priyanka R.; Bhuyar, Sonal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Abnormal uterine bleeding (AUB) is considered as one of the most common but yet a challenging problem presenting to the gynaecologist. AUB is defined as abnormal changes occurring in the frequency of menstruation, duration of flow or amount of blood loss. Its impact on women’s physical, social, emotional and maternal quality of life is substantial. A detailed clinical assessment, thyroid profile, measurement of endometrial thickness on sonography and histopathological evaluation of endometrium is crucial for diagnosing the underlying causes of AUB. Methods: A cross-sectional study was conducted over 18 months at a tertiary healthcare centre. This study enrolled 245 patients aged over 35 years presenting with complaints of AUB. Clinical data of all patients were collected via structured interviews and examinations. They were subjected to thyroid function test and ultrasonography for endometrial thickness. Endometrial samples were obtained through dilatation and curettage (D and C) and analysed histopathologically. The clinical presentation was correlated with histopathological findings of the endometrium. Results: The majority of patients were in the age group 41-45 years (31.8%), with a mean age of 44.8 years. Menorrhagia was found to be the most common bleeding pattern (57.1%), followed by menometrorrhagia (30.2%) and postmenopausal bleeding (12.7%). Endometrial hyperplasia without atypia was the predominant histopathological finding (63.3%), followed by proliferative phase (17.1%) and secretory phase (14.3%). Endometrial carcinoma was identified in 3.7% of cases. Conclusions: Histopathological examination is the gold standard investigation for patients presenting with AUB. Clinicopathological correlation aids in accurate diagnosis, early detection of premalignant lesions and appropriate management, thereby improving patient outcomes.